Personal cultural orientations: Looking beyond scale development and validation - Sharma, Piyush (2016)
Piyush Sharma is a professor of marketing in the School of Marketing at Curtin University in Perth, Australia. He has about thirty years’ overall professional experience in industry and academics. Before joining the School of Marketing at Curtin University in Jan 2014, he served as Associate Professor and Director ‐ Asian Centre for Branding and Marketing at the Hong Kong Polytechnic University (PolyU). Besides teaching and supervising undergraduate and postgraduate business students at PolyU, he also as the Deputy Program Director for the Hong Kong MBA program (2009‐ 12) and Associate Dean/Coordinator ‐ Internationalization (2010‐12) at PolyU. Prof Sharma’s research covers services and international marketing, cross‐cultural consumer behavior, counterfeit purchase behavior, and self‐regulation. His work appears in the Journal of International Business Studies, Journal of the Academy of Marketing Science, Journal of Service Research, Journal of Services Management, Journal of Services Marketing, Journal of Business Research, European Journal of Marketing, Journal of Advertising, Journal of Marketing Management, Marketing Intelligence & Planning, Journal of Retailing and Consumer Services, Journal of International Consumer Marketing, and Journal of Euromarketing, among others. In his paper published in the Journal of the Academy of Marketing Science in 20101 , Prof Sharma addressed several concerns about prior cross‐cultural studies that used Hofstede’s national scores to operationalize his five cultural factors at individual level; namely ecological fallacy, unidimensionality and limited evidence of construct validity and measurement equivalence. Specifically, this paper reconceptualized Hofstede’s five cultural factors as ten personal cultural orientations and developed a new 40‐item scale to measure them. It also established the validity, reliability, and cross‐cultural measurement equivalence of the new scale and discussed its advantages over other scales. In this talk, Prof Sharma will briefly introduce this paper and then share his current research that extends his personal cultural orientations framework in a wide variety of contexts, including intercultural service encounters, service experience evaluation, country‐of‐origin and consumer ethnocentrism, counterfeit purchase and consumption, self‐regulation and regulatory focus etc. He will also discuss the managerial implications of his ongoing work and directions for future research.